Role of Imaging in Bronchoscopic Lung Volume Reduction Using Endobronchial Valve: State of the Art Review. Issue 3 (May 2021) - Dass, Chandra; Goldbach, Alyssa; Dako, Farouk; Kumaran, Maruti; Steiner, Robert; Criner, Gerard J.
Abstract : Chronic obstructive pulmonary disease (COPD) is becoming one of the leading causes of mortality and morbidity throughout the world. The National Emphysema Treatment Trial demonstrated that lung volume reduction surgery can improve pulmonary function, exercise capacity, and quality of life in select subgroups of patients with COPD. In recent years, few bronchoscopic lung volume reduction (BLVR) procedures have undergone clinical trials with the goal of establishing an effective and safe alternative approach for reducing hyperinflation in patients with severe emphysema who are symptomatic despite optimal medical management, but are poor surgical candidates. Of these BLVR procedures, only deployment of 1-way endobronchial valves (EBVs) has the largest pool of scientific data available to date to support its clinical utility. Two EBV systems have been food and drug administration-approved within the last year to meet the clinical demands of this select group of patients with COPD. On the basis of the results of multiple randomized clinical trials, the recommendations of the original 2016 Expert Panel Report on BLVR usage criteria of EBV have been updated in 2019. The outcome of EBV therapy is maximized in certain image-based COPD phenotypes. Imaging plays a major role in patient selection, target lobe identification, and in the management of postprocedural adverse events. With the expected widespread use of EBV therapy in the coming years, knowledge and familiarity of the Role of Imaging in BLVR using EBVs is essential for radiologists attempting to make meaningful contribution toward improving clinical outcomes.